The Influence of Husband Support and Information Sources on Cervical Cancer Screening Behavior - Ilham Salam; Sudirham Sudirham; Tika Bela Sari (Journal of Public Health and Pharmacy, 2024)
Introduction: Cervical cancer is still the "cold-blooded killer" in the world because most cases develop without any real symptoms in the early stages. Globally, cervical cancer is the fourth most common cancer in women. Around 90% of the 342,000 deaths from cervical cancer occur in developing countries, including Indonesia. Cervical cancer is a disease that can be prevented through early detection. However, the number of women who undergo VIA examinations is still very small, so there are still many women who suffer from cervical cancer. This study aims to determine the direct and indirect influence of husband's support and sources of information on VIA examination behavior in an effort to detect cervical cancer early in women of childbearing age at the North Tondano District Health Center in 2023. Methods: The research design used was cross-sectional. The population in this study was women of childbearing age who were registered at the Pasar Minggu District Health Center. The total sample was 53 respondents. The analytical method used is Structural Equation Modeling (SEM) using SmartPLS 2.0 and SPSS 23. Results: The results of the study show that the behavior variable for VIA examinations in an effort to detect cervical cancer early in women of childbearing age (WUS) at the North Tondano District Health Center is directly influenced by husband's support (47.1%) and information sources (31.3%), while other factors that were not considered influenced the VIA examination behavior variable by 21.6%. Conclusion: In conclusion, husband's support and effective information dissemination significantly enhance VIA examination participation, aiding in the early detection and prevention of cervical cancer among women of childbearing age. It is recommended to increase outreach in the community to promote early cancer detection.